Сексуальная функция молодой украинской семьи: социологический аспект - Медина, Т. (Социология: теория, методы, маркетинг, 2000)
One of the specific features related to sexual functions of modern young family is extended limits of individual freedom in sexual relations and gradual transition to common sexual moral. Because of separation of sexuality from conception, this aspect of family life becomes especially important. The article presents information about the main problems related to the sexual relations started before a family has been formed and to planning of modern young family: beginning of sexual life, attitudes toward pre-marriage sexual relations, time correspondence between a beginning of sexual relations and a decision about being married, how satisfaction with family life depends of satisfaction with sexual relations, as well as the most popular (among modern young families) contraception means.